Mental health in the war on terror : culture, science, and statecraft - Aggarwal, Neil Krishan (Columbia University Press, 2015)
This study finds that mental-health and biomedical professionals have created new forms of knowledge and practice in their desire to understand and fight terrorism, and in the process, psychiatrists and psychologists have either worked uncritically to protect state interests or labored to protect undesirable populations from state control. Professional interpretation, like all interpretations, is subject to cultural forces. Drawing on cultural psychiatry and medical anthropology, the author analyzes the influence of the war on terror in the transformation of definitions for normal and abnormal behavior.